2015
DOI: 10.1007/s11738-014-1760-0
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress condition increases root to shoot ratio via alteration of carbohydrate partitioning and enzymatic activity in rice seedlings

Abstract: To understand the underlying mechanism for plasticity in root to shoot ratio (R/S) in response to drought stress, two rice cultivars, Zhenshan97 (drought susceptible) and IRAT109 (drought resistant), were grown hydroponically, and R/S, carbohydrate concentration and partitioning, and activities of enzymes for sucrose conversion in seedlings exposed to drought stress condition (DS) imposed by polyethylene glycol 6000 were investigated. The R/S significantly increased under DS in comparison with that under well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
195
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(216 citation statements)
references
References 44 publications
12
195
1
8
Order By: Relevance
“…This corroborates with the findings of [1], [5], [13]- [15]. Though many factors influence the drought tolerance of crops, these factors are not independent, but interact with one another.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This corroborates with the findings of [1], [5], [13]- [15]. Though many factors influence the drought tolerance of crops, these factors are not independent, but interact with one another.…”
Section: Discussionsupporting
confidence: 92%
“…The studies of [15] revealed that under drought conditions the plasticity of the plants allow increased allocation of several primary metabolites to roots while decreasing allocation to shoots.…”
Section: Effect Of Water Stress On Root/shoot Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Greater reductions in root growth compared to shoot growth under drought stress have been documented in several studies (Azhiri-Sigari et al 2000, Cui et al 2008). The reports indicated that the root growth response to drought stress depends on stress duration and stress development rate, and on the allocation of carbohydrates to the roots (Xu et al 2015). In the first year of our study, the roots probably contained lower amounts of carbohydrates; therefore, they experienced a greater reduction in dry weight compared to the shoots.…”
Section: Discussionmentioning
confidence: 55%
“…'IR64' has been known as drought sensitive rice cultivar (Prakash et al, 2016). The high root to shoot ratio is to increase water uptake (Xu et al, 2015). Root characteristics become important for selection of rice cultivars (Baloch et al, 2012).…”
Section: Discussionmentioning
confidence: 99%